Antioxidant, Antimicrobial and Antitopoisomerase Screening of the Stem Bark Extracts of Ardisia compressa - Ramirez-Mares, Marco Vinicio; Sanchez-Burgos, Jorge Alberto; Hernandez-Carlos, Beatriz (Pakistan Journal of Nutrition, 2010)
The in vitro antioxidant, antimicrobial and antitopoisomerase activities of crude Methanolic (Me) and Hexane (He) extracts of the stem bark of Ardisia compressa (AC) were investigated. Free radical-scavenging activity against 2,2-Diphenyl-1-picrylhydrazyl (DPPH) was evaluated, acid ascorbic was used as reference standard. Antimicrobial activity was determined using the agar diffusion method; the bacteria K. pneumoniae, E. coli, S. epidermidis and the fungus C. albicans. Controls employed were chloranphenicol (30 μg) and nystatin (100 units). Topoisomerase inhibition was determined by a clone-forming assay, which uses yeast (S. cerevisiae) strains as a model. Controls included dimethyl sulfoxide (1.66%); campothecin (50 μg/ml), etoposide (100 μg/ml) and sobuzoxane (150 μg/ml). Ascorbic acid was a substantially more powerful antioxidant than the extracts from the stem bark of AC. The Antiradical Efficiency (AE) of ascorbic acid was 249-fold that for He and 8.3-fold that for Me. Only the growth of Klebsiella pneumoniae was inhibited by Me (MIC = 1.875 mg/ml) and He (MIC = 0.9375 mg/ml), while the growth of the other strains were not inhibited. He extract not showed antitopoisomerase activity. Me extract showed antitopoisomerase activity (-15.3%). Open column chromatography of the methanolic extract was conducted and fourteen fractions were collected and tested. Fractions VI (-21.55%), X (-42.49%), XI (-97.68%), XII (-52.34%) and XIII (-35.97%) showed antitopoisomerase I activity and fraction XIV (-79%) antitopoisomerase II (poison) activity. These results suggest that Me extract of the stem bark of A. compressa could be promising in its potential usefulness for treatment of cancer and deserves further investigation.